2020
DOI: 10.1007/s11205-020-02502-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Migration Pay Off in Later Life? Income and Subjective Well-Being of Older Migrants in Europe

Abstract: This study examines whether intra-European migration pays off in terms of income and subjective well-being (SWB) for migrants aged 50 + who are now growing old abroad and in what way their SWB is associated with their relative income position. Using panel data from the Survey of Health, Ageing and Retirement in Europe allows us to go beyond the classical comparison with the native reference group and draw on information about respondents who stayed in the place of origin (‘stayers’). Our findings indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The impact for people moving between similarly developed places is mixed, with persons moving between developed countries benefiting more than people moving between developing countries (IOM 2013;Hendriks et al 2018). Examples of such migration flows where positive outcomes were observed are Western Europeans moving to Northern America, Australia, or New Zealand; UK residents moving to Ireland (Hendriks et al 2018); migrants aged 50+ who moved between European countries (Gruber and Sand 2021); and German emigrants who moved to other (mostly Western) European countries (Erlinghagen 2011). Examples of migration flows where no positive outcomes were observed are individuals moving within South Asia or between Anglo-Saxon countries (Hendriks et al 2018).…”
Section: International Migrantsmentioning
confidence: 99%
“…The impact for people moving between similarly developed places is mixed, with persons moving between developed countries benefiting more than people moving between developing countries (IOM 2013;Hendriks et al 2018). Examples of such migration flows where positive outcomes were observed are Western Europeans moving to Northern America, Australia, or New Zealand; UK residents moving to Ireland (Hendriks et al 2018); migrants aged 50+ who moved between European countries (Gruber and Sand 2021); and German emigrants who moved to other (mostly Western) European countries (Erlinghagen 2011). Examples of migration flows where no positive outcomes were observed are individuals moving within South Asia or between Anglo-Saxon countries (Hendriks et al 2018).…”
Section: International Migrantsmentioning
confidence: 99%
“…In addition, our results showed that not-working older adults were more likely to report poor SRH. Working status is an indicator of financial condition and study shows older migrants are positively associated with their relative income status and they are more likely found to have a low income [ 95 ]. Yet, interestingly, a study found that Hispanics who immigrated at the age of 18 still had sharp declines in health condition after the age of 50 years, because of discrimination, underinsurance and low-paying work environment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies suggest that Eastern European migrants to Western societies are primarily motivated by the desire to improve their financial well-being (Strockmeijer, de Beer, and Dagevos 2019). Economic factors, such as low earnings, the need to support their families, unfavorable economic conditions in their home countries, and high unemployment, drive their migration choices (Bauer and Zimmermann 1999; Burrell 2010; Kahanec and Pytliková 2017; Felbo-Kolding, Leschke, and F. Spreckelsen 2019; Gruber and Sand 2022). These studies frequently adopt a rational choice model, conceptualizing migrants as economically motivated individuals who carefully consider the costs, benefits, and risks associated with migration decisions, compared to the potential financial gains from working abroad.…”
Section: Literature and Theoretical Considerations Of Migration Risk ...mentioning
confidence: 99%